2008
DOI: 10.1902/jop.2008.080152
|View full text |Cite
|
Sign up to set email alerts
|

Pain Perception and Anxiety During Scaling in Periodontally Healthy Subjects

Abstract: Although most patients experienced limited pain during scaling, a significant relationship was found between pain and smoking. Women and patients aged 30 to 40 years are likely to be more anxious during scaling. The question, "How fearful are you of having your teeth cleaned?" may not adequately cover all aspects of anxiety for patients' experience of pain during scaling. Clinicians should determine individual treatment approaches to reduce patients' fear, pain, and anxiety related to scaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 48 publications
3
51
0
3
Order By: Relevance
“…Women reported more dental anxiety than did men, as shown in previous studies (3,23,26). It could be attributed to the fact that men refuse to report symptoms they consider weak or unmasculine and tend to silently cope with anxiety.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Women reported more dental anxiety than did men, as shown in previous studies (3,23,26). It could be attributed to the fact that men refuse to report symptoms they consider weak or unmasculine and tend to silently cope with anxiety.…”
Section: Discussionsupporting
confidence: 78%
“…Please use the numbers from the scale for the first three questions. Therefore, in our study, the patients were asked to complete a questionnaire consisting of only these seven questions, as was done previously by Chung et al and Guzeldemir et al (3,21). The anxiety questionnaire scores ranged from 7 to 35 (Fig.…”
Section: Dental Anxiety Questionnaire Sheetmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Dental anxiety was found to have a direct relationship with pain perception. 13 Rhudy and Meagher 14 suggested that the pain reactivity is modulated by emotional stress. In addition, Loggia et al 15 revealed changes in pain pathways on neuroimaging techniques with a negative emotional state.…”
mentioning
confidence: 99%